Analysis of the applicability of the technical quality standards in public administration in NTCGP 1000:2009 municipal mayor Neiva - Huila (2014)
This research paper, one conceptualizes Public Management Model Management according to the Colombian Technical Standard 1000:2009 NTCGP Public Management, defines, characterizes and generalizes the Balanced Scorecard as a management tool, which allows by means of a strategy to achieve the desired objectives of an organization, then exposes public sector cases where this tool is implemented and the range achieved by the same. As a citizen of Neiva - Huila and according to the shortcomings observed in each of the processes of the Municipality of the City, the author describes and analyzes the current conditions of the managerial model of Public Management Authority (Development, scope and failures), which is the Internal Control system rocked and based on the Balanced Scorecard proposed improvement actions that lead to continued strengthening of the quality management system of the administrative unit in question.